Dying to quit : why we smoke and how we stop - Brigham, Janet (Joseph Henry Press, 1998)
Someone dies of a tobacco-related disease, somewhere in the world, every 10 seconds. Why do so many of us - one in every three persons worldwide - smoke? And what can science tell us about how we can stop? This book follows the smoking-life of a young woman hoping to quit, and explores the myths and mysteries of addiction.